MG-143 Age is significantly associated with the bone marrow engraftment in patients with allogeneic stem cell transplantation. (4th December 2015) - Lin, Hanxin; Stringer, Randa; Dyck, Jacob; Sjaarda, Jenny; Li, Wangping; Freitag, Andreas P; Pare, Guillaume; Carter, Ronald F; Sadikovic, Bekim
Abstract : Objectives: Allogeneic stem cell transplantation is a curative therapy for patients with haematological malignancies and nonmalignant haematological disorders. Measuring the bone marrow engraftment via donor chimerism following transplantation is often used as a predictor for the overall survival. However, prognostic factors associated with bone marrow engraftment are poorly understood. The objective of this study is to evaluate the effect of age, gender and the recipient-donor relationship on the extent of bone marrow engraftment following transplantation and thereby provide more precise counselling to patients. Methods: The bone marrow engraftment was routinely monitored using the multiplex fluorescent short tandem repeat analysis. Complete engraftment is defined as ≥95% of both donor-derived white blood cells and T cells. Data from a cohort of 194 patients with various conditions and up to 10 years of follow up was retrospectively analysed. Logistic regression and survival analyses were performed using the R statistic software. Results: 64.9% of patients reached complete engraftment, ˜70% out of which achieved this milestone within 2 years post-transplantation; but 6.3% of these patients relapsed. Gender and recipient-donor relationship (related or not, same sex or not) did  not have significant effect on the probability and the time for reaching complete engraftment. Age was inversely related to the probability of complete engraftment. The older the patient was, the less likely he/she achieved complete engraftment (p value 0.0015), and the longer time took for reaching complete engraftment (p value 0.0009). Conclusion: Age is significantly associated with the likelihood and time for reaching complete engraftment.